A Historical background and distinguishing features of Ahkam-ul-Quran: احکام القرآن للجصاص کا تاریخی پس منظر اور امتیازی خصوصیات - Ali, Sabir; Ahmed, Dr. Shabir; Ali, Khawaja Arshid (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Al-Jassas (370 305) AH/917 AD-AH/981 AD. full name Abu Bakr Aḥmad ibn ʿAli al-Razi al-Jassas was a Hanafite scholar,mostly known as the commentator of Al-Hassafs work on Qadi (jurisprudence). Ahkam-ul-Quran is an important book of Imam Abu Bakr al-Jassas. Ahkam-ul-Quran’s study is of great significance as it marks the first attempt to assess the terminology and the norms of the Usul with a scientific method. Al-Fusus is divided into one hundred and five sections and it comprises four volumes but different publishers have combined 4 vol in two volumes. Almost all topics later involved in Usul books are examined by Jassas with the rational and narrated evidence in this special book. He provides a lot of significant information about the importance, power, and usage of the reason (Aqal) in Islamic thought. By drawing on the concept of the Aqal he is seen to have agreed with Mu’tazili view. The different opinions of Usul scholars have been widely investigated by Jassas in this work using a plain language. Imam Jassas employs a dialectical method to explain the ideas he prefers about a matter in dispute. The methodological approach taken in this study is similar to Shafi’s in al-Risalah. However, Imam Jassas heavily criticizes Shafi under the following title of al-Fusul: Dalil al-Khitab, Bayan, and Nasikh.